4CPS-029 Adherence to medication and salt restriction and blood pressure control among hypertensive patients. (2nd March 2018) - terline, D de; Diop, BI; N'Guetta, R; Koffi, F; Houenassi, M; Limbolé, E; Kuate, L Mfeukeu; Nhavoto, C; Empana, JP; Jouven, X; Antignac, M
Abstract : Background: Sub-Saharan Africa is experiencing a rising burden of hypertension. Antihypertensive medications and salt-restriction diet are the cornerstone of effective hypertension control. Purpose: We therefore, assessed adherence to medication and salt restriction in 12 sub-Saharan countries and studied their relationship with blood pressure (BP) control among hypertensive patients. Material and methods: We conducted a cross-sectional survey in urban clinics of 12 sub-Saharan countries (Benin, Democratic Republic of Congo, Guinea, Mozambique, Niger, Togo, Cameroon, Congo (Brazzaville), Gabon, Côte d'Ivoire, Mauritania, Senegal). Data collected on demographics, treatment and standardised BP measures were made among the hypertensive patients attending the clinics. BP control was defined as BP <140/90 mmHg and hypertension grades were defined according to European Society of Cardiology guidelines. Poor adherence was defined as a score <8 on the validated 8-Item Morisky Medication Adherence Scale (MMAS 8) completed by the patients. We developed a scale (ranging from 0 to 9) to assess salt consumption: poor adherence to salt restriction was defined as a score ≥2. The association between adherence to medication and salt restriction and BP control was investigated using multilevel logistic regression analysis adjusting for age, sex and countries. Results: A total of 2198 hypertensive patients (mean age 58.4±11.8 years; 39.9% male) were included. Among these patients, 77.4% had uncontrolled BP, 34.0% were poorly adherent to salt restriction, 64.4% were poorly adherent to medication and 24.6% had poor adherence to both. Poor adherence to salt restriction (OR: 1.33, 95% CI: 1.03 to 1.72), medication (OR: 1.56, 95% CI: 1.25 to 1.93) or both (OR: 1.91, 95% CI: 1.39 to 2.66) was related to uncontrolled BP. Moreover, poor adherence to both medication and salt restriction was related to 1.52 fold (95% CI: 1.04 to 2.22), 1.8 fold (95% CI: 1.22 to 2.65) and 3.08 fold (95% CI: 2.02 to 4.69) increased the likelihood of hypertension grade 1, 2 and 3 respectively. Conclusion: High levels of non-adherence to medication and salt restriction were noted in this urban sub-Saharan study. Both were significantly associated with uncontrolled BP, representing major opportunities for intervention to improve hypertension control in sub-Saharan Africa. No conflict of interest